Molecular expression of the NHX1 gene in response to hydric and saline stress in young plants of Eucalyptus grandis - García, Ximena; Gamboa, María Cecilia; Krauskopf, Erwin (BOSQUE, 2019)
Plants are exposed to several types of abiotic stress that affect their development. Among these, salinity and drought affect large areas of land worldwide. Chile does not escape this reality, estimating that 49.1 % of the territory have these characteristics. Due to the boom of forestry in Chile, the development of strategies aimed at using these low-quality soils becomes imperative. In this context, understanding the mechanisms involved in salt and drought stress in tree species such as Eucalyptus grandis has become essential. Thus, the permeability of the cell membrane was established by electrolyte leakage, recognizing that the plants exhibit damage after 12 hours of salt stress and after 10 hours of drought stress. Furthermore, the expression of a specific gene (NHX1) was determined on Eucalyptus grandis plants subjected to salt and water stress, establishing a rise in its expression in foliar and root tissue. From a physiological perspective, the observed response to abiotic stress is similar to that described for other plant species that have a shorter life cycle. Additionally, the increased expression of a specific gene (NHX1) under conditions of abiotic stress confirms it as a potential candidate for genetic improvement programs in woody species for the selection of individuals tolerant to these types of stress.